2021
DOI: 10.1287/isre.2020.0971
|View full text |Cite
|
Sign up to set email alerts
|

Does Money Talk? The Impact of Monetary Incentives on User-Generated Content Contributions

Abstract: Many platforms use monetary incentives to encourage user-generated content (UGC) contributions. The empirical evidence, however, is contradictory: monetary incentives are shown to either increase or decrease contribution. We make the first attempt to build a unified theoretical model to understand the complex nature of the impact of monetary incentives. We consider contributors differentiated not only by their attitudes toward monetary incentives but also by their effectiveness to attract audience. We identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Moreover, few researches have explored the impact of introducing monetary incentives on both UGC quality and platform profits. Our paper is closely related to the work of Ren et al (2012), Jain and Qian (2021), Liu and Feng (2021). Ren et al (2012), Jain and Qian (2021) analytically study the design of platforms' incentive schemes.…”
Section: Contributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, few researches have explored the impact of introducing monetary incentives on both UGC quality and platform profits. Our paper is closely related to the work of Ren et al (2012), Jain and Qian (2021), Liu and Feng (2021). Ren et al (2012), Jain and Qian (2021) analytically study the design of platforms' incentive schemes.…”
Section: Contributionsmentioning
confidence: 98%
“…Qiao et al (2021) argue that monetary incentives can undermine intrinsic motivations because when they are offered, individuals shift their focus from intrinsic satisfactions to the incentives, the salience of the intrinsic motivations decreases. Sun et al (2017) and Liu and Feng (2021) point out that monetary incentives may also undermine contributors' image-related motivations, because monetary incentives may dilute the signaling effect of contribution behavior on prosocial preferences and increase that on greediness.…”
Section: Motivations Of Ugc Contributorsmentioning
confidence: 99%
“…Studies have found that when rewards impair the self-determination of people by pressuring them to think, feel, or behave in an externally controlled way, motivation is negatively affected (Deci and Ryan, 1985;Liu and Feng, 2021). In this context, Khern-am-nuai et al ( 2018) as well as Burtch et al (2018), for instance, observed that the introduction of financial rewards in an online review system leads to less reviewing effort.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…First, our results suggest that self-contained rewards represent an effective alternative to financial rewards. Financial rewards come with direct marginal costs, they often crowd out reviewer effort, and they induce a positivity bias into numerical ratings (Khern-am-nuai et al, 2018;Liu and Feng, 2021). Some platforms, such as Yelp and Amazon, even prohibit financial incentives to stimulate user-generated content.…”
Section: Implications For Practicementioning
confidence: 99%
“…The effect of extrinsic incentives on prosocial behavior has been widely studied in the literature of economics, psychology, and information systems [Newman and Shen, 2012, Gneezy and Rustichini, 2000, Liu and Feng, 2021. In this study, we focus on the effect of crypto rewards on "first-time" donations (instead of the long-term consequences of monetary incentives).…”
Section: Introductionmentioning
confidence: 99%